Actualization of Science Literacy in the Freedom Era of Studying in the City of Semarang - Deni Setiawan; Ria Budi Ashari; Isa Ansori; Moh. Fathurrahman; Siti Maryatul Kiptiyah; Dewi Nilam Tyas (Postgraduate, University of Mataram, 2023)
Scientific literacy is part of implementing the independent curriculum in learning activities at SD Nasima. The research objective was to determine the independent curriculum implementation for grades 1, 2, 4, and 5 at SD Nasima, primarily scientific literacy. This study uses a qualitative method with a descriptive approach. The design used is a case study which means the researcher reveals and analyzes the problem in depth to get specific results. The subjects in this study were teachers, students, and school principals at Nasima Elementary School. Data collection uses primary and secondary sources. Primary sources include observations and interviews, while secondary sources come from books, journals, and scientific articles. The stages of data analysis include critical analysis, interpretation, and conclusions data validity techniques using source triangulation. The study results show that there is scientific literacy in the implementation of the independent curriculum, using learning resources and learning processes, and finding obstacles in its application.